The Study of Determinant Factors of Customer Satisfiction with Industrial Products in Helmand Province, Afghanistan - Mohammad Naim Kakar; Dr. Ali Ahmad; Mujtaba Amin; Amanullah Niazai (Emerging Frontiers Library for The American Journal of Management and Economics Innovations, 2025)
This research aims to evaluate customer satisfaction with industrial products in Helmand province, Afghanistan, and identify which dimensions and factors of the marketing mix have the most significant impact on customer satisfaction. Sixty-five questionnaires were gathered from customers who visited industrial production companies within the past three days to collect data. The collected data was analysed using SPSS 26.0 and OLS and correlation techniques. The findings indicate that all dimensions of marketing (7Ps) have a positive and significant relationship with customer satisfaction. Among the variables, price was identified as the most influential factor affecting customer satisfaction compared to other variables. Based on the model, the obtained R Square is 0.451, which means that the independent variables can explain 45.1% of the variance in the dependent variable (customer satisfaction). Overall, the study's results show that all independent variables significantly impact the dependent variable